2021
DOI: 10.21831/cp.v40i2.35190
|View full text |Cite
|
Sign up to set email alerts
|

Secondary School Teachers’ Knowledge and Practices About Constructive Feedback: Evidence From Karachi, Pakistan

Abstract: Teachers’ knowledge, conceptualization and actual practices in the classroom influence students’ academic performance. The present study sought to determine the existing practices and knowledge of teachers about constructive feedback, and to find how the knowledge of teachers would predict teachers’ feedback practices in classroom.  A quantitative approach with survey research design was adopted to collect the data from the respondent through feedback knowledge questionnaire. The participants of the study were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Unlike, the small-scale survey in Ethiopia (Dessie and Sewagegn, 2019), this study found that teacher beliefs about feedback did have statistically significant relationships to practices, a result reported elsewhere Kyaruzi et al, 2018;Aslam and Khan, 2021). Like Kyaruzi et al (2018), this study found that formative feedback practices were supported by improvement-oriented beliefs about the purpose of feedback.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Unlike, the small-scale survey in Ethiopia (Dessie and Sewagegn, 2019), this study found that teacher beliefs about feedback did have statistically significant relationships to practices, a result reported elsewhere Kyaruzi et al, 2018;Aslam and Khan, 2021). Like Kyaruzi et al (2018), this study found that formative feedback practices were supported by improvement-oriented beliefs about the purpose of feedback.…”
Section: Discussioncontrasting
confidence: 71%
“…The same study reported that the use of praise in feedback predicted feedback actions that protected students from negative evaluative consequences. A survey of 390 Pakistani teachers, using the TCoF, found that endorsement of feedback as encouragement led to greater use of protective evaluation practices such as giving positive messages to students and not making critical comments (Aslam and Khan, 2021). Hofstede et al (2010).…”
Section: Relationship Of Feedback Perceptions To Self-reported Practicesmentioning
confidence: 99%
“…He also stated that teachers must update their expertise and have a distinctive teaching technique. According to Aslam and Khan (2021), instructors at all levels must constantly refresh their knowledge and abilities in evaluation methods and strategies in order to stay current with the newest educational developments. To summarise, competent teachers will engage in building their value systems and, as a result, strengthening their practises in order to continually improve the performance of their students.…”
Section: Discussionmentioning
confidence: 99%
“…Negative feedback can be an effective tool for students to identify areas of weakness in their performance, allowing them to improve their skills. It is important, however, for feedback to be given constructively to avoid discouragement or demotivation (Aslam & Khan, 2021). Constructive feedback also provides opportunities for growth by enabling students to develop strategies to address problems and improve their performance (Omer & Abdularhim, 2017).…”
Section: Ways To Give Negative Feedback Constructivelymentioning
confidence: 99%